Bioinformatics And Functional Genomics - Jonathan Pevsner (Wiley India, 2009)
It is a textbook for undergraduate students, graduate students, and anyone involved in biomedical research. The first third of this book covers bioinformatics, a new field at the interface of the ongoing revolutions in molecular biology and computers. A focus of this new discipline is the use of computer databases and computer algorithms to study proteins and genes, including sequence alignment, database searches, and phylogeny. The middle third of this book focuses on functional genomics including approaches such as gene expression profiling and proteomics that are used to study cellular function. The last third of the book is on genomics which is the study of the collection of DNA that comprises an organism, using the tools of bioinformatics. This portion of the book spans the tree of life from viruses to prokaryotes and eukaryotes, including a description of the human genome in health and disease. The book is complemented by lavish illustrations and more than 500 figures and tables-fifty of which are entirely new to this edition. Each chapter includes a Problem Set, Pitfalls, Boxes explaining key techniques and mathematics/statistics principles, Summary, Recommended Reading, and a list of freely available software. It serves as an excellent single-source textbook for advanced undergraduate and beginning graduate-level courses in the biological sciences and computer sciences. It is also an indispensable resource for biologists in a broad variety of disciplines who use the tools of bioinformatics and genomics to study particular research problems; bioinformaticists and computer scientists who develop computer algorithms and databases; and medical researchers and clinicians who want to understand the genomic basis of viral, bacterial, parasitic, or other diseases.